Sosialisasi Dan Pendampingan Digital Marketing Guna Meningkatkan Pemasaran UMKM Desa Talang - Moch. Rafie Pratama; Evan Saka Akhfan; Arya Dharma Syahputra; Anandah Amirah; Hayu Desthia; Hendra Maulana (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
Currently Indonesia is in the industrial revolution 4.0 where technological changes affect living habits, ways of working and communicating with one another. In other words, this era is the main axis in life. The changes in this era also have an impact on the economic sector towards a digital economy. Visible changes are the convenience that people get in accessing online services such as ordering food through applications, shopping for necessities online, selling online to studying at home online. In Talang village, Nganjuk district, only 2 micro, small and medium enterprises that have been recorded have run their businesses using digital marketing. Therefore, KKNT 66 KKNT students have the goal of improving the micro, small and medium business sector by providing socialization as well as digital marketing assistance to micro, small and medium enterprises. So that it can make it easier for micro, small and medium enterprises in Talang village to expand the market and develop their business. After conducting outreach and assistance to micro, small and medium enterprises in Talang village, the result was an increase of 4 small and medium micro businesses that had registered their business in digital marketing. While the other 4 still haven't got it. There are several small and medium micro businesses that are not willing to register their business for digital marketing.